Effects of increasing glycerol and dried distillers grains with solubles on the growth performance and carcass characteristics of finishing pigs - Duttlinger, A.W.; Benz, J.M.; Houser, Terry A.; Tokach, Michael D.; Dritz, Steven S.; Prusa, K.J.; DeRouchey, Joel M.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,160 barrows (PIC, initially 68.4 lb) were used in a 97-d study to determine the influence of glycerol and dried distillers grains with solubles (DDGS) on growing-finishing pig performance, carcass characteristics, and fat quality. Pigs were blocked by weight and randomly allotted to 1 of 6 dietary treatments with 7 replications per treatment. Pigs were fed corn-soybean meal-based diets arranged in a 2 × 3 factorial with main effects of glycerol (0, 2.5, or 5%) and DDGS (0 or 20%). Overall (d 0 to 97), there were no glycerol × DDGS interactions (P > 0.12) for growth performance, carcass characteristics, and carcass fat iodine value (IV). Increasing glycerol did not affect (P > 0.14) ADG or F/G. Adding 20% DDGS to the diet did not affect ADG. However, pigs fed diets with 20% added DDGS had greater (P < 0.02) ADFI resulting in poorer (P < 0.01) F/G than pigs fed diets with no DDGS. For carcass characteristics, pigs fed increasing glycerol tended to have increased (linear, P < 0.11) yield. Pigs fed diets with added DDGS had increased (P < 0.01) jowl fat, belly fat, and backfat IV compared with pigs fed diets with no DDGS. However, increasing dietary glycerol tended to decrease (linear, P < 0.11) backfat IV. In conclusion, feeding pigs 20% DDGS worsened F/G and increased carcass fat IV, whereas feeding glycerol did not influence growth performance but tended to improve carcass yield and reduce backfat IV.
Keywords: Dried distiller grains with solubles; Glycerol; Growing-finishing pig